Pulmonary Embolism and Posterior Circulation Infarcts Following Position Change from Prone to Supine during Cervical Spine Surgery: A Case Report - Adhikary, Anirban B.; Gupta, Priyanka; Jadhav, Ramanand V.; Mahaseth, Ranjay (Journal of Neuroanaesthesiology and Critical Care, 2025)
Acute massive pulmonary embolism (PE) is a lethal condition unless promptly detected and managed. Diagnosing and managing massive PE during the perioperative period can be challenging due to overlapping clinical signs with other complications. This case report highlights the challenges of diagnosing and managing a massive PE in a patient with morbid obesity who underwent instrumentation of the cervical spine at multiple levels and developed cardiac arrest while turning the patient supine from the prone position. With the help of focused cardiac ultrasound, we suspected PE, which was later confirmed on imaging. Postoperative brain imaging also confirmed the presence of multiple embolic infarcts in the occipital and cerebellar hemispheres.
Keywords: pulmonary embolism; prone position; cervical vertebral fusion; vertebral artery insufficiency; posterior circulation brain infarction